The Earth Microbiome Project: The Meeting Report for the 1st International Earth Microbiome Project Conference, Shenzhen, China, June 13th–15th 2011. Issue 2 (September 2011) - Gilbert, Jack; Bailey, Mark; Field, Dawn; Fierer, Noah; Fuhrman, Jed; Hu, Bin; Jansson, Janet; Knight, Rob; Kowalchuk, George; Kyrpides, Nikos; Meyer, Folker; Stevens, Rick
Abstract This report details the outcome of the 1st International Earth Microbiome Project Conference. The 2-day conference was held at the Kingkey Palace Hotel, Shenzhen, China, on the 14th–15th June 2011, and was hosted by BGI (formally the Beijing Genomics Institute). The conference was arranged as a formal launch for the Earth Microbiome Project, to highlight some of the exciting research projects, results of the preliminary pilot studies, and to provide a discussion forum for the types of technology and experimental approaches that will come to define the standard operating procedures of this project.